The Onset of Recrystallization in Polar Firn, Summit, Greenland, 2022 - Ayobami Ogunmolasuyi; Andrii Murdza; Ian Baker (Arctic Data Center, 2023)
Constraining the onset of dynamic recrystallization and its effects on the mechanical properties of firn is crucial for modeling the firn densification process. To that end, experiments have been conducted on firn samples from 13 meter (m) depth in a Greenland firn core. Changes in the microstructural parameters were examined using a combination of polarized optical examination of thin sections and micro-computed tomography (micro-CT) of bulk samples. The mean grain diameter decreases rapidly at the early stage of deformation and levels off as the strain levels increase, while the grain area distribution indicates an increase in the frequency of smaller grains as the strain increases. Analyses of micro-CT reconstructions show an increase in density, due to a decrease in porosity and specific surface area. The results show that dynamic recrystallization occurs in firn under creep, with its onset occurring at a strain of ~12%. The recrystallization leads to both a reduction in grain size and a change in the fabric, indicating that recrystallization occurs by nucleation and growth.